Superficial and Deep Macula Vessel Density in Healthy, Glaucoma Suspect, and Glaucoma Eyes. Issue 6 (June 2021) - El-Nimri, Nevin W.; Manalastas, Patricia Isabel C.; Zangwill, Linda M.; Proudfoot, James A.; Bowd, Christopher; Hou, Huiyuan; Moghimi, Sasan; Penteado, Rafaella C.; Rezapour, Jasmin; Ekici, Eren; Shoji, Takuhei; Ghahari, Elham; et al.
Abstract : Precis: Macular superficial capillary plexus (SCP) vessel density is more informative than deep capillary plexus (DCP) vessel density for the detection of glaucoma. Purpose: The purpose of this study was to characterize optical coherence tomography angiography macular SCP and projection-resolved DCP vessel densities and compare their diagnostic accuracies with ganglion cell complex (GCC) thickness in healthy, glaucoma suspect, and glaucoma eyes. Materials and Methods: Sixty-eight eyes of 44 healthy subjects, 26 eyes of 16 preperimetric glaucoma suspects, and 161 eyes of 124 glaucoma patients from the Diagnostics Innovations in Glaucoma Study with good quality high-density 6×6 mm 2 macula optical coherence tomography angiography images were included. The diagnostic accuracy of SCP vessel density, projection-resolved DCP vessel density and GCC thickness were compared among groups. Results: Mean whole image vessel density (wiVD; % of area occupied by vessels containing flowing blood) in the SCP layer was highest in healthy eyes (49.7%), followed by glaucoma suspect eyes (46.0%), and glaucoma eyes (40.9%) ( P <0.001). Mean wiVD in the DCP layer was similar in healthy (50.6%), glaucoma suspect (47.3%), and glaucoma eyes (45.7%) ( P =0.925). Diagnostic accuracy of both GCC thickness and SCP wiVD was significantly higher than DCP wiVD for classifying healthy and glaucoma eyes [adjusted area under the receiver operating characteristic curve (95% confidence interval): GCC=0.86 (0.72, 0.94), SCP=0.80 (0.66, 0.91) and DCP=0.44 (0.30, 0.57)] ( P <0.001). Conclusions: SCP vessel densities have better diagnostic accuracy for detecting glaucoma than DCP vessel densities. Although the diagnostic accuracy of the macula SCP is relatively modest, it is more informative than the DCP.